THE FINANCIAL PERFORMANCE ANALYSIS OF INDIAN IT COMPANIES, FOCUSING ON TCS, INFOSYS - Jana, Rathindra Nath; Patil, Dr. R. K. (The journal of contemporary issues in business and government, 2021)
Indian firms have adapted their strategies over the years in response to rising competition, economic uncertainty, technological progress, and rising customer demand. Organizations in all sectors of India's economy are through a period of transition that necessitates the use of digital technology. It's true that "Digital Transformation" is now the standard. India also has a flourishing startup scene, which is luring investors from all around the world. Consumer and business adoption of digital technologies in India have been boosted by the government's "Digital India" initiatives. Let's examine what's going on in India's IT sector and how it's evolving.